Does social media foster students' entrepreneurial intentions? - Nguyen Thi Loan; Rowena Monzon Libo-on; Truong Tuan Linh; Nguyen Khanh Nam (Cogent Business & Management, 2024)
This study examined the impact of social media usage on students' entrepreneurial intentions, making a novel contribution by extending the Theory of Planned Behavior (TPB). Specifically, two additional variables were introduced into the TPB framework: social media and perceived risk. Employing the Generalized Structural Equation Modeling (GSEM) method, interview data were analysed from 362 students in two Vietnamese provinces, Thai Nguyen and Thanh Hoa. Results revealed that attitudes, subjective norms, and perceived behavioral control all positively influenced students' entrepreneurial intentions. Second, perceived risk acted as a limiting factor on students' entrepreneurial intentions. Third, social media exerted a positive influence on students' entrepreneurial intentions through both direct and indirect channels. Notably, the relationship between social media and perceived behavioral control was influenced by students' levels of experience. Specifically, experience enhanced this relationship most significantly among students with moderate experience, followed by those with high experience. In contrast, students' low experience did not significantly affect the relationship between social media and perception.
Keywords: 650; Entrepreneurial intentions; social media; students